2023
DOI: 10.1371/journal.pone.0290256
|View full text |Cite
|
Sign up to set email alerts
|

A capacitive laser-induced graphene based aptasensor for SARS-CoV-2 detection in human saliva

Geisianny Moreira,
Hanyu Qian,
Shoumen Palit Austin Datta
et al.

Abstract: SARS-CoV-2 virus induced CoVID-19 pandemic has accelerated the development of diagnostic tools. Devices integrated with electrochemical biosensors may be an interesting alternative to respond to the high demand for testing, particularly in contexts where access to standard detection technologies is lacking. Aptamers as recognition elements are useful due to their stability, specificity, and sensitivity to binding target molecules. We have developed a non-invasive electrochemical aptamer-based biosensor targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For example, the LOD for SARS-CoV-2 detection using an electrochemical aptasensor is <1100 copies per mL, 149 while for a capacitive laser-induced graphene-based aptasensor, it stands at 1790 copies per mL. 150 These LODs translate to a detection capability that is 2 orders of magnitude beyond the acceptable diagnostic sensitivity for SARS-Cov-2 (1.0 × 10 6 genome copies per mL) according to the World Health Organization. 151 As for protein detection, an on-chip integrated graphene aptasensor achieves an LOD of 160 aM for COVID-19 neutralizing antibodies in serum, 152 which is 5 orders of magnitude lower than the minimum target concentration (30 pM) in patients.…”
Section: Aptamer-based Sensor For the Detection And Analysis Of Evsmentioning
confidence: 99%
“…For example, the LOD for SARS-CoV-2 detection using an electrochemical aptasensor is <1100 copies per mL, 149 while for a capacitive laser-induced graphene-based aptasensor, it stands at 1790 copies per mL. 150 These LODs translate to a detection capability that is 2 orders of magnitude beyond the acceptable diagnostic sensitivity for SARS-Cov-2 (1.0 × 10 6 genome copies per mL) according to the World Health Organization. 151 As for protein detection, an on-chip integrated graphene aptasensor achieves an LOD of 160 aM for COVID-19 neutralizing antibodies in serum, 152 which is 5 orders of magnitude lower than the minimum target concentration (30 pM) in patients.…”
Section: Aptamer-based Sensor For the Detection And Analysis Of Evsmentioning
confidence: 99%
“… 192 Moreira et al demonstrated an aptasensor based on EIS. 193 The proposed aptasensor for the detection of SARS-CoV-2 in human saliva was fabricated using LIG. A comprehensive analysis of EIS signals identified the optimal response along with suitable cutoff frequencies.…”
Section: Transduction Mechanisms Of Gr-based Electroanalytical Devicesmentioning
confidence: 99%
“…LIG can be functionalized with the material of interest (recognition element), where changes in the electrochemical response of LIG occur due to the chemical interaction between the recognition element and target analyte in solution. In the last decade since the discovery of LIG, this material has been used for targeting a wide variety of sensors, for example: bacteria [22], viruses [23], sugars [20], and ions [24]. This material is simple to fabricate, and numerous portable devices have been developed using custom form factors that meet sampling needs.…”
Section: Introductionmentioning
confidence: 99%